Optimization and Improvement on Adhesion Control for HXD1 Locomotive - ZHANG Guoshun; LIU Zhenhua; GAO Shoucong; ZHANG Zhengfang; HU Yunqing (机车电传动)
Aim to the problems of adhesion lacking for localization HXD1 electric locomotives start-up and speed acceleration at large ramp in Xikang segment of Xi’an Railway Bureau, speed calculation methods was improved. Based on auto-regressive moving average model(ARMA) optimal estimation filter theory, creep speed differential estimates was optimized, which improved traction performance. Traction test of Xikang segment showed that the optimization and improvement of software could enhance the adhesion utilization of HXD1 electric locomotives with a good effect.